SlBEL11 affects tomato carotenoid accumulation by regulating SlLCY-b2 - He, Yan; Wang, Yu; Zhang, Mengzhuo; Liu, Guangsen; Tian, Cong; Xu, Xiangbin; Pan, Yonggui; Shi, Xuequn; Zhang, Zhengke; Meng, Lanhuan (Frontiers in Nutrition, 2022)
Extensive data have demonstrated that carotenoid accumulation in tomato fruit is influenced by environmental cues and hormonal signals. However, there is insufficient information on the mechanism of its transcriptional regulation, as many molecular roles of carotenoid biosynthetic pathways remain unknown. In this work, we found that the silence of the BEL1-like family transcription factor (TF) BEL1-LIKE HOMEODOMAIN 11 (SlBEL11) enhanced carotenoid accumulation in virus induced gene silencing (VIGS) analysis. In its RNA interference (RNAi) transgenic lines, a significant increase in the transcription level for the lycopene beta cyclase 2 (SlLCY-b2) gene was detected, which encoded a key enzyme located at the downstream branch of the carotenoid biosynthetic pathway. In Electrophoretic mobility shift assay (EMSA), SlBEL11 protein was confirmed to bind to the promoter of SlLCY-b2 gene. In addition, the dual-luciferase reporter assay showed its intrinsic transcriptional repression activity. Collectively, our findings added a new member to the carotenoid transcriptional regulatory network and expanded the functions of the SlBEL11 transcription factor.